Developing index for stroke risk - Ng, Lee Koon (Nanyang Technological University, 2021)
The stroke risk scoring model is a powerful tool to predict the risk of stroke. It can determine the specific treatment and measure and predicts the outcome. Several scoring systems make use of different risk factors. The risk factor includes in this study comprised of Age, BMI, Cholesterol Ratio, HBA1c, Systolic Pressure, Pulse Pressure, Smoking, Alcohol, and Atrial Fibrillation. The objective of this FYP is to formulate a stroke risk scoring model based on various research papers and to test out the model using real-time data. The model can then be compared with an established model such as Framingham Stroke risk(FSRS), ATRIA, and CHADS2. All of the 10-risk factors are proven to have a positive correlation to the increase of stroke risk. With a base scoring model, more risk factors can be added to the model. With a strong link established between PWV and stroke risk, a recommendation for PWV to be added to the model for further study.